p-Phenyleneethynylene molecular wires: influence of structure on photoinduced electron-transfer properties. - Wielopolski, Mateusz; Atienza, Carmen; Clark, Timothy; Guldi, Dirk Michael; Martín, Nazario (Chemistry - A European Journal, 2008)
A series of donor-acceptor arrays (exTTF-oPPE-C ) containing π-conjugated oligo(phenyleneethynylene) wires (oPPE) of different length between π-extended tetrathiafulvalene (exTTF) as electron donor and fullerene (C ) as electron acceptor has been prepared by following a convergent synthesis. The key reaction in these approaches is the bromo-iodo selectivity of the Hagihara-Sonogashira reaction and the deprotecting of acetylenes with different silyl groups to afford the corresponding donor-acceptor conjugates in moderate yields. The electronic interactions between the three electroactive species were determined by using UV-visible spectroscopy and cyclic voltammetry. Our studies clearly confirm that, although the C units are connected to the exTTF donor through π-conjugated oPPE frameworks, no significant electronic interactions are observed in the ground state. Theoretical calculations predict how a simple exchange from C=C double bonds (i.e., oligo(p-phenylenevinylene) to C≡C triple bonds (i.e., oPPE) in the electron donor-acceptor conjugates considerably alters long-range electron transfer. Photoexcitation of exTTF-oPPE-C leads to the following features: a transient photoproduct with maxima at 660 and 1000 nm, which are unambiguously attributed to the photolytically generated radical-ion-pair state, [exTTF -oPPE- C ]. Both charge-separation and charge-recombination processes give rise to a molecular-wire behaviour of the oPPE moiety with an attenuation factor (β) of (0.2 ±0.05) Å . © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.